Serum Sphingosine 1-Phosphate (S1P): A Novel Diagnostic Biomarker in Early Acute Ischemic Stroke - Liu, Jia; Sugimoto, Kazuo; Cao, Yuanbo; Mori, Masahiro; Guo, Li; Tan, Guojun (Frontiers in Neurology, 2020)
Background: Sphingosine 1-phosphate (S1P) is a lipid metabolite, which mediates various physiological processes, including vascular endothelial cell function, coagulation/thrombosis, and angiogenesis. As a result, S1P may contribute to the pathogenesis of stroke.Objective: To evaluate the diagnostic value of serum S1P in acute stroke.A total of 72 patients with ischemic stroke, 36 patients with hemorrhagic stroke, and 65 controls were enrolled. Serum S1P was detected by enzyme-linked immunosorbent assay (ELISA).Receiver operating characteristic curve analysis demonstrated that serum S1P could discriminate ischemic stroke from hemorrhagic stroke in both total population and subgroup analysis of samples obtained within 24 h of symptom onset (subgroup <24h ) (Area under curve, AUC Total = 0.64, P = 0.017; AUC Subgroup<24h = 0.91, P < 0.001) and controls (AUC Total = 0.62, P = 0.013; AUC Subgroup<24h = 0.83, P < 0.001). Furthermore, S1P showed more power than high-density lipoprotein cholesterol (HDL-C) in discriminating ischemic stroke from controls in total population (P S1P = 0.013, P HDL-C = 0.366) and in the subgroup analysis (i.e., <24 h; P S1P < 0.001, P HDL-C = 0.081). Additionally, declined serum S1P associated with cervical artery plaques (P = 0.021) in controls and dyslipidemia (P = 0.036) and milder neurological impairment evaluated by National Institute of Health Stroke Scale (NIHSS, P = 0.047) in ischemic stroke group. The present study firstly investigated the diagnostic value of serum S1P in acute stroke. The decreased serum S1P may become a potential biomarker for early acute ischemic stroke and reflect the disease severity.